أدوات الخطاب عند رايدينغ (Ryding) في قصة قصيرة "أرنوب والكذب" - Sabiila, Diyanah Hanin; Taufiq, Mirwan Akhmad (Proceedings of International Conference on Islamic Civilization and Humanities, 2024)
Literature is a work of art that is expressed through language media. In general, literary works in Arabic are divided into three, namely prose, poetry, and drama. One of the prose literary works is short stories. In this study, the researchers will examine the discourse markers initiated by Ryding in the short story entitled "أرنوب والكذب" written by Ahmad Samir. The method used in this study is a descriptive qualitative in which the researchers as the main instrument aimed to describe the Arabic discourse markers contained in the short story. The results of this study showed that the following are the discourse markers used in the story: waw, inna wa akhwatuha and waw isti’naf. For the waw, it was found twelve words, for inna it was found seven words, and for waw isti’naf it was found in two words.